1995
DOI: 10.1159/000133972
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the origin of a G-positive band within the secondary constriction region of human chromosome 9

Abstract: We report on a so-called rare variant where a G-positive band was sandwiched within the secondary constriction (qh) region of chromosome 9 and is apparently different from previous cases when characterized by the fluorescence in situ hybridization technique. The major differences included duplication of β-satellite and satellite III DNA sequences and bands 9q 13q21.1, without duplication or inversion of the alphoid sequences. Based on the reported cases, at least four types of variations can be accounted for. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Verma et al 39 described an inverted duplication 9qh in a prenatal case. Inverted duplications of 9p10-q12 were also reported by Wang and Miller 25 and Macera et al (Type II) 5 using FISH with a pan-a-satellite probe and a chromosome 9-specific b-satellite DNA probe. The inversion type C described by Samonte et al 7 is similar to our 9qh+ with inversion type var3, while their types A, B and D were not detected in our study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Verma et al 39 described an inverted duplication 9qh in a prenatal case. Inverted duplications of 9p10-q12 were also reported by Wang and Miller 25 and Macera et al (Type II) 5 using FISH with a pan-a-satellite probe and a chromosome 9-specific b-satellite DNA probe. The inversion type C described by Samonte et al 7 is similar to our 9qh+ with inversion type var3, while their types A, B and D were not detected in our study.…”
Section: Discussionsupporting
confidence: 64%
“…8 In summary, 12 heteromorphic patterns and the normal variant of the pericentric region of chromosome 9 are described. Previous studies attributed the extensive degree of variability in this region to unequal meiotic exchanges involving the various classes of repetitive sequences in the centromeric region 5,7,25 and to unequal exchanges involving stretches of homologous DNA sequences in the proximal short and long arms of chromosome 9. 15 The results of the present study would support such an assumption.…”
Section: Heteromorphisms On Hsamentioning
confidence: 99%
See 1 more Smart Citation
“…Type A inversion consist of breakpoints within the α and β satellite DNA regions; type B consist of breakpoints the β satellite DNA region 9q13; type C involve breakage within the β and classical satellite DNA regions, and type D have breakpoints within the α and classical satellite DNA regions. Like these, obviously, reshuffling of satellite DNA sequences occurred, which has given rise to a variety of heteromorphisms whose clinical significance remains obscure (Samonte et al, 1996), few types of pericentric inversion have been observed due to the variable breakpoints within the qh regions, but their implications have also remained obscure (Verma et al, 1993;Macera et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The variation of chromosomes with qh have been classified into two classes, termed "size" and "inversion" heteromorphisms (Verma et al, 1978). A third type of variation has surfaced wherein an additional G-positive or G-negative bands is sandwiched within the qh region of chromosome 9 and 1 (Macera et al, 1995;Verma et al, 1997). If Giemsa is used, the dark band is called G-band or G-positive band, and the light band is named G-negative band.…”
Section: Introductionmentioning
confidence: 99%